Developing genome-editing strategies to ameliorate HbE/beta-thalassaemia - Badat, M (2021)
The thalassaemias are the most common monogenic disorders worldwide. Both α- and β-thalassaemia are caused by genetic mutations that result in a decrease in globin gene expression and protein synthesis. The more clinically significant of the two disorders, β-thalassaemia is mainly caused by point mutations in the β-globin gene or proximal sequences. Patients develop severe anaemia early in life and are dependent on life-long blood transfusions. The relative excess free α-globin chains in developing erythroblasts causes apoptosis and necrosis, resulting in ineffective erythropoiesis and the resulting severe phenotype. Decades of careful clinical observational studies have shown that individuals with severe β-thalassaemia who co-inherit α-globin gene mutations often have a mild or asymptomatic phenotype. This is especially, but not limited to, individuals with HbE/β-thalassaemia which causes half of all severe β-thalassaemia worldwide. The α- and β-globin gene clusters are among the most finely characterised loci in the human genome, and this understanding of gene regulation in normal and pathological contexts allows the development of tailored therapeutic strategies. In this study, I have to tried to use this knowledge to develop two therapeutic strategies to cure β-thalassaemia. The first aims to tunably reduce α-globin expression by editing its main enhancer, MCS-R2, to restore globin chain balance in patients with severe β-thalassaemia. The second aims to recapitulate the asymptomatic carrier β-thalassaemia trait state by using new technology to repair the HbE mutation in-situ.